Transformasi Identitas Bobotoh Persib Bandung (Studi Fenomenologi Dalam Aksi Koreografi Tribun “Save Rogingya” - HAYUSTIRO TIRO TIRO (MediaKom : Jurnal Ilmiah Komunikasi, 2019)
AbstractBobotoh is the nickname of supporters of Persib Bandung soccer club from West Java. Almost as an entity, supporters of Persib Bandung are West Javanese and ethnic Sundanese, although there are also some subgroups of Bobotoh which do not depart from Sundanese ethnic identity. Of course, there are various kinds of Bobotoh individuals who are diverse, different economic status, social and education are not obstacles for each individual to unite to support the pride of West Java, Persib Bandung. Bobotoh is one of the supporters with the largest base in Indonesian football. With a high level of loyalty, always present in Lapanhan to give support when the game Persib Bandung plays, in the home game that is always boisterous and total in supporting and always present in the away match Persib Bandung play. Currently the form of Bobotoh support in matches is not always subject to specific matters relating to football, but themes outside of football are also present as work material in the field stands. In 2017 Bobotoh held a choreography in the form of "Save Rohingya" at the Stadium Si Jalak Harupat Soreang in Stadium at the east stand. This was meant by Bobotoh also concerned with the humanitarian themes which at that time became the "current issue" that the Rohingya ethnic conflict that occurred in Myanmar was part of the solidarity of the Bobotoh.Keywords: Bobotoh Persib, Football, Choreography, Supporting, Identity